Extracellular ubiquitin levels are increased in coronary heart disease and associated with the severity of the disease. (2nd April 2020) - Ji, Yiqun; Yao, Jialu; Zhao, Yunxiao; Zhai, Juping; Weng, Zhen; He, Yang
Abstract: Aim: This study aimed to evaluate concentration of plasma extracellular ubiquitin (UB) in coronary heart disease (CHD) patients and its correlation with the disease severity. Methods: Levels of UB and stromal cell-derived factor-1a (SDF-1a) were measured in 60 healthy controls and 67 CHD cases. Coronary atherosclerosis was assessed with Gensini scoring system. Spearman correlation was used to evaluate the correlation between UB and low-density lipoprotein cholesterol (LDL-C), C-reactive protein (CRP), creatine kinase-MB (CK-MB), cardiac troponin I (cTnI) or SDF-1a. The receiver-operating characteristic (ROC) curve was established to assess the predictive value of UB. Results: Plasma UB levels were significantly higher in CHD patients than in controls ( p < .0001), and the levels in those with acute myocardial infarction (AMI) were higher than stable angina pectoris (SAP) and unstable angina pectoris (UAP) groups (both p < .01). UB was also positively correlated with Gensini score, CRP, CK-MB and cTnI in CHD. ROC analysis of UB showed that the area under the curve (AUC) were 0.711 (95%CI, 0.623–0.799) and 0.778 (95%CI, 0.666–0.890) for CHD and acute coronary syndrome (ACS), respectively. Plasma SDF-1a levels were elevated in CHD patients but showed no significant correlation with UB concentration or the severity of the disease. Conclusion: Plasma UB concentration was increased in CHD and the change of UB levels may reflect the progression of CHD.